The Effects of Mandatory Speed Limits on Crash Frequency - A Causal Machine Learning Approach - Maike Metz-Peeters (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
This study analyzes the effects of binding speed limits on crash frequency on German motorways. Various geo-spatial data sources are merged to a new data set providing rich information on roadway characteristics for 500-meter segments of large parts of the German motorway network. The empirical analysis uses a causal forest, which allows to estimate the effects of speed limits on crash frequency under fairly weak assumptions about the underlying data generating process and provides insights into treatment effect heterogeneity. The paper is the first to explicitly discuss possible pitfalls and potential solutions when applying causal forests to geo-spatial data. Substantial negative effects of three levels of speed limits on accident rates are found, being largest for severe, and especially fatal crash rates, while effects on light crash rates are rather moderate. The heterogeneity analysis suggest that the effects are larger for less congested roads, as well as for roads with entrance and exit ramps, while heterogeneity regarding shares of heavy traffic is inconclusive. – – Diese Studie untersucht die Auswirkungen örtlich begrenzter Geschwindigkeitsbeschränkungen auf die Unfallhäufigkeit auf deutschen Autobahnen. Verschiedene räumliche Daten werden zu einem neuen Datensatz zusammengeführt, der umfangreiche Informationen über Fahrbahnmerkmale für 500-Meter Segmente großer Teile des deutschen Autobahnnetzes enthält. Die empirische Analyse verwendet einen Causal Forest, mit dem die Auswirkungen von Geschwindigkeitsbeschränkungen auf Unfallhäufigkeit unter relativ schwachen Annahmen über den zugrundeliegenden datengenerierenden Prozess geschätzt werden können und der Einblicke in die Heterogenität der Effekte ermöglicht. Die Studie ist die erste, die das Problem des räumlichen Overfittings und mögliche Lösungen im Kontext des kausalen Machine Learnings diskutiert. Es werden deutliche negative Effekte von drei Stufen von Geschwindigkeitsbeschränkungen auf Unfallraten geschätzt, wobei die Auswirkungen auf schwere und insbesondere tödliche Unfälle am größten sind, während die Effekte auf leichte Unfälle eher moderat sind. Die Heterogenitätsanalyse deutet darauf hin, dass die Effekte auf weniger überlasteten Straßen, sowie auf Straßen mit Ein- und Ausfahrten stärker sind, während die Heterogenität in Bezug auf den Anteil des Schwerverkehrs keine eindeutigen Ergebnisse liefert.
Keywords: R41; R42; R48; 330; Crash frequency; speed limits; German Autobahn; causal machine learning; causal forest; spatial machine learning